2016
DOI: 10.5380/ce.v21i2.44006
|View full text |Cite
|
Sign up to set email alerts
|

Contexto De Ambiente De Trabalho Entre Enfermeiras Assistenciais Em Hospital Universitário

Abstract: Objetivou-se analisar o ambiente de trabalho favorável à prática profissional de enfermeiros em hospital universitário público. Estudo transversal e quantitativo, realizado com 60 enfermeiros assistenciais, com o questionário Nursing Work Index – Revised. Os dados foram coletados entre novembro 2014 e janeiro de 2015. Dentre os pesquisados, 45 (75%) enfermeiros consideravam-se satisfeitos com seu trabalho. Todos os 12 setores da instituição apresentaram características favoráveis à prática do enfermeiro nos as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The participants' profile corroborates other studies performed with the nursing team in neonatal care environments, which have shown a prevalence of women, nursing technicians, young adults with experience in the area (time of education and of service and specialization) and viable workload (14)(15)(16)(17)(18)(19) . Upon assessment of nursing practice environment in NICU (Table 1), a predominance of favorable aspects is perceived in four of the five subscales of PES, a fact which was demonstrated by a multicenter study with 1247 NICU nurses of North American hospitals (20) , whose scores ranged from 1.93 and 3.79, with an overall mean of 2.88 (±0.32), characterizing favorable environments for nursing team practice (20) .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The participants' profile corroborates other studies performed with the nursing team in neonatal care environments, which have shown a prevalence of women, nursing technicians, young adults with experience in the area (time of education and of service and specialization) and viable workload (14)(15)(16)(17)(18)(19) . Upon assessment of nursing practice environment in NICU (Table 1), a predominance of favorable aspects is perceived in four of the five subscales of PES, a fact which was demonstrated by a multicenter study with 1247 NICU nurses of North American hospitals (20) , whose scores ranged from 1.93 and 3.79, with an overall mean of 2.88 (±0.32), characterizing favorable environments for nursing team practice (20) .…”
Section: Discussionsupporting
confidence: 85%
“…Another important aspect is related to excessive workload as a stressor agent, which is pointed by study participants and is the theme of several articles (15,(26)(27) . This workload may be classified as physiological, psychic, biological, mechanical, physical, and chemical and may also have severe outcomes and lead to illnesses among nursing team workers (28) .…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis to the studies, it was clear that unfavorable environments are associated with worse outcomes for patients and professionals (29)(30)36,42) . On the other hand, favorable environments for the nursing practice guarantee better results for professionals, patients and institutions (10,27,34) . Diverse authors have identified greater Rev Gaúcha Enferm.…”
Section: Discussionmentioning
confidence: 99%
“…Work environment also includes effective leadership, available resources, professional participation, trust and interdisciplinary It has been emphasised that nursing professionals must have sufficient skills to be able to provide quality care and exert influence on their work environment. 30 An enhanced work environment foments autonomy of practice and communication between nurses and doctors, improving the quality of care. 1 A number of studies have also shown that the work environment determines the health conditions of patients.…”
Section: Highlightsmentioning
confidence: 99%
“…It has been emphasised that nursing professionals must have sufficient skills to be able to provide quality care and exert influence on their work environment 30 . An enhanced work environment foments autonomy of practice and communication between nurses and doctors, improving the quality of care 1 .…”
Section: Introductionmentioning
confidence: 99%